Safety and immunogenicity of high-dose trivalent inactivated influenza vaccine in adults 50–64 years of age. Issue 51 (16th December 2015) - DiazGranados, Carlos A.; Saway, William; Gouaux, James; Baron, Mira; Baker, Jeffrey; Denis, Martine; Jordanov, Emilia; Landolfi, Victoria; Yau, Eddy
Highlights: A high-dose inactivated influenza vaccine (IIV-HD) is available for adults ≥65years. IIV-HD and a standard-dose vaccine (IIV-SD) were evaluated in adults 50–64 years. Immune responses were generally stronger for the IIV-HD. Reactogenicity was higher for IIV-HD, but it was well tolerated. IIV-HD may improve immune responses to influenza in adults 50–64 years. Abstract: Background: Individuals 50–64 years of age have reduced immune responses to influenza vaccines. The current study examined whether a high-dose inactivated trivalent influenza vaccine (IIV3-HD) might improve immune responses over a standard-dose inactivated influenza vaccine (IIV3-SD) in this age group. Methods: This was a multicenter, observer-blinded, randomized, active-controlled phase II trial. Adults 50–64 years of age were randomized 1:1 to receive IIV3-HD or IIV3-SD. Hemagglutination inhibition titers were measured before and 28 days after vaccination. Reactogenicity was recorded for 7 days after vaccination and adverse events for 28 days. Results: 148 participants received IIV3-HD and 152 received IIV3-SD. For all vaccine strains, day 28 geometric mean hemagglutination inhibition titers were significantly higher in the IIV3-HD group than in the IIV3-SD group (geometric mean titer ratio [95% confidence interval (CI)] = 1.43 [1.04–1.97] for A/H1N1, 1.65 [1.21–2.25] for A/H3N2, and 1.60 [1.23–2.08] for B). Seroconversion rates were significantly higher in the IIV3-HD group than in the IIV3-SD group for strains A/H3N2 and B but not A/H1N1 (difference [95% CI] = 13.5% [4.76–22.0] for A/H3N2, 23.1% [11.7–33.6] for B, and −0.2% [−9.66 to 9.18] for A/H1N1). The post-vaccination seroprotection rate was significantly higher in the IIV3-HD group than in the IIV3-SD group for strain B but not for strains A/H1N1 or A/H3N2 (difference = 9.1% [2.95–15.7] for B, 2.0% [−0.907 to 5.68] for A/H1N1, and 0.6% [−3.14 to 4.43] for A/H3N2). Reactogenicity was higher in the IIV3-HD group than in the IIV3-SD group, but reactions were mostly of low intensity, transient, and self-limited. Rates of unsolicited adverse events were similar between groups. No serious AEs, AEs leading to early withdrawal, or deaths were reported. Conclusions: The study suggests that in adults 50–64 years of age, IIV3-HD may improve immunogenicity compared to IIV3-SD while maintaining an acceptable safety profile.